Pendampingan Petani melalui Edukasi Keuangan Hijau sebagai Pilar Kemandirian Ekonomi untuk Mewujudkan Swasembada Pangan - Faradina Zevaya; Rahma Nurjanah; Putri Intan Suri; Jaya Kusuma Edy; Etik Umiyati (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
This community service program aims to promote local economic self-reliance and achieve food self-sufficiency through strengthening green financial literacy in Tangkit Baru Village, Muaro Jambi Regency, Jambi Province. This village is known as an agro-tourism area based on pineapple commodities, which has great potential to support regional food security and the development of a green economy. However, this potential has not been fully utilized due to the community’s low literacy in green finance, limited access to sustainable financing, and the absence of environmentally friendly agricultural waste processing technology. The program is designed to provide practical solutions through five main stages: proposal preparation, establishment of the implementing team and involved stakeholders, green literacy and green financial management education, report preparation and publication, and program evaluation. The educational component will focus on farmers’ understanding of the concept of green finance, as well as their ability to record and manage farm business finances in a simple manner. In addition, the program will facilitate strategic partnerships with green financial institutions and involve students through the ProIDE program as part of an integrative effort to encourage youth participation in sustainable development. The targeted objectives of this activity include increasing farmers’ understanding of green financial literacy, establishing farmer groups based on a green economy, and creating an integrated model linking agro-tourism and food self-sufficiency based on green finance. With a transformative and collaborative approach, this program is expected to become a model of sustainable village empowerment based on a green economy and contribute to achieving the Sustainable Development Goals (SDGs) at the local level.